An honorable design of S-type vertical axis wind turbine. Issue 1 (2nd January 2022) - Gandhar, Abhishek; Gautam, Sarthak; Atray, Abhishek; Chauhan, Akash; Bhardwaj, Utkarsh
Abstract: This research paper proposed a nascent design of savonius vertical axis wind turbine for the purpose of generating electricity. After the study of various available research, various parameters were taken into consideration to model a working wind turbine producing desired amount of energy. The following text contains account of available literature and then those concepts were applied to implement wind as a permanent source of energy.